MathGroup Archive 2011

[Date Index] [Thread Index] [Author Index]

Search the Archive

Re: How to find one expression in terms of another

  • To: mathgroup at smc.vnet.net
  • Subject: [mg119746] Re: How to find one expression in terms of another
  • From: Bob Hanlon <hanlonr at cox.net>
  • Date: Mon, 20 Jun 2011 08:05:17 -0400 (EDT)
  • Reply-to: hanlonr at cox.net

Element is not used the way that you think. See documentation.

$Assumptions = True;

T1 = (t1 - ((u x1)/c^2))/Sqrt[1 - (u^2/c^2)];

T2 = (t2 - ((u x2)/c^2))/Sqrt[1 - (u^2/c^2)];

dT = T2 - T1;

FullSimplify[dT /. t2 -> dt + t1]

(c^2*dt + u*(x1 - x2))/(c^2*Sqrt[1 - u^2/c^2])

FullSimplify[dT /. t2 -> dt + t1, Element[c, Reals]]

(c^2*dt + u*(x1 - x2))/(Sqrt[(c - u)*(c + u)]*Abs[c])

$Assumptions = Element[c, Reals];

FullSimplify[dT /. t2 -> dt + t1]

(c^2*dt + u*(x1 - x2))/(Sqrt[(c - u)*(c + u)]*Abs[c])


Bob Hanlon

---- Jacare Omoplata <walkeystalkey at gmail.com> wrote: 

=============
I want to find dT in terms of dt. They are given below.



In[1]:= Element[{x1, x2, t1, t2, u, c}, Reals]

Out[1]= (x1 | x2 | t1 | t2 | u | c) \[Element] Reals

In[3]:= T1 = (t1 - ((u x1)/c^2))/Sqrt[1 - (u^2/c^2)]

Out[3]= (t1 - (u x1)/c^2)/Sqrt[1 - u^2/c^2]

In[4]:= T2 = (t2 - ((u x2)/c^2))/Sqrt[1 - (u^2/c^2)]

Out[4]= (t2 - (u x2)/c^2)/Sqrt[1 - u^2/c^2]

In[5]:= dT = T2 - T1

Out[5]= -((t1 - (u x1)/c^2)/Sqrt[1 - u^2/c^2]) + (
 t2 - (u x2)/c^2)/Sqrt[1 - u^2/c^2]

In[6]:= dt = t2 - t1

Out[6]= -t1 + t2


If I knew that dT can be written in terms of dt in the form,
dT = a dt + b,
Can I use Mathematica to find a and b?

I tried using  Solve[dT == a dt + b, dt], but that gives an error.

If I didn't know that dT can be expressed this way, can I still
express it in terms of dt ?



  • Prev by Date: Re: Why doesn't TrueQ return True here?
  • Next by Date: Re: How to find one expression in terms of another expression?
  • Previous by thread: Possibilities to speed up export to swf
  • Next by thread: suppressing error messages